Successful use of adalimumab as a conservative treatment for bilateral knee lipoma arborescens in patient with psoriatic juvenile idiopathic arthritis – case report and review of literature - Frkovic, Marijan; Kujundzic, Magdalena; Cavka, Mislav; Jelusic, Marija (Frontiers in Pediatrics, 2022)
Lipoma arborescens (LA) is a chronic, slowly progressive intra-articular mass associated with the proliferation of synovial villi. It can affect one or several joints and has been commonly described in adults with degenerative joint disease. Most patients have been diagnosed with MRI and/or biopsy findings and are usually treated with partial or total synovectomy. Case reports of LA in children, particularly with juvenile idiopathic arthritis (JIA) are scarce. We present a 16-year-old girl with a prolonged course of psoriatic JIA (initial bilateral knee affection and subsequent involvement of wrists and elbows combined with psoriatic scalp lesions) and LA of both knees. Psoriatic JIA has been diagnosed at the age of 13, with immediate start of methotrexate (MTX) therapy. Several weeks later, magnetic resonance imaging (MRI) of the right knee, performed with the aim of the most swollen joint additional evaluation, revealed synovial changes consistent with LA; arthroscopic biopsy confirmed the diagnosis. After two years of MTX treatment, despite the successful maintenance of minimal JIA activity except for repetitive bilateral knee swelling, control MRI revealed bilateral knee lesions identical to those described two years earlier in the right knee. Following the step-up approach in JIA treatment, the TNF inhibitor adalimumab was added in therapy. Finally, six months later, clinical reduction of both knees swelling was noticed with almost complete LA regression in the right, and partial regression in the left knee, confirmed by final MRI control. A conservative approach, including TNF inhibitors, instead of usually performing synovectomy, seems like a reasonable option in cases of LA with underlying JIA.